Development of Food Pyramid Game Tools as a Stimulation of Balanced Nutrition Knowledge for Children Aged 5-6 Years - Cahyani, Avrilia Dwi; Pramono, Pramono; Tirtaningsih, Munaisra Tri (Universitas Negeri Malang, 2024)
Balanced nutritional status in early childhood affects growth and development. Children's knowledge about balanced nutrition will affect the application of nutritional information in everyday life. The purpose of this research is to produce a food pyramid game tool product that is feasible according to material experts, media experts, user experts, small-scale tests, and field tests as well as teaching materials in stimulating balanced nutritional knowledge of children aged 5-6 years. This research includes development research (RnD) with the SYNTHESIS model which includes: 1) Needs analysis, 2) Identify aspiration model, 3) Develop initial model, 4) Expert test, 5) Small scale test, and 6) Field test. The small-scale test involved 6 group B kindergarten children, while the field test used 24 group B kindergarten children. The results showed that the food pyramid game tool showed very feasible results, this can be seen from the percentage of material experts 82.9%, media experts 83.5%, user experts 93.6%, small scale tests 100%, and field tests 95.8%. The validation results show that the food pyramid game tool is categorized as very feasible to be used as a stimulation of balanced nutritional knowledge for children aged 5-6 years. Keywords: Playground Equipment; Food Pyramid; Balanced Nutrition